Posisi Tasawuf Teoretis dalam Tinjauan Logika Tafsir Al-Qurâan - Gama, Cipta Bakti (Tanzil : Jurnal Studi Al-Quran, 2016)
ThisÂ  paperÂ  addressesÂ  theÂ  issueÂ  ofÂ  howÂ  theÂ  positionÂ  ofÂ  theoreticalÂ  SufismÂ  inÂ  the interpretationÂ  ofÂ  theÂ  Qurâan.Â  DepartingÂ  fromÂ  someÂ  reasonsÂ  forÂ  rejectingÂ  theÂ  validity ofÂ  SufisticÂ  methodÂ  ofÂ  QurâanicÂ  interpretationÂ  (isharÄ«Â  method),Â  theÂ  authorÂ  seesÂ  the needÂ  toÂ  explainÂ  theÂ  natureÂ  ofÂ  theoreticalÂ  SufismÂ  andÂ  itsÂ  positionÂ  basedÂ  onÂ  theÂ  logic ofÂ  QurâanicÂ  exegesis.Â  SomeÂ  importantÂ  pointsÂ  whichÂ  theÂ  authorÂ  triesÂ  toÂ  showÂ  inÂ  this paper are five principles, as follows: First, the theoretical Sufism could be positioned asÂ  aÂ  sourceÂ  ofÂ  interpretationÂ  ofÂ  theÂ  Qurâan.Â  Second,Â  shuhÅ«dÂ  âirfÄnÄ«Â  whichÂ  isÂ  theÂ  main foundation of theoretical Sufism could be positioned as a source of interpretation of the Qurâan, in the context of the disclosure of meaning, not in the explanation of it. Third, theoretical Sufism might be used as a source or indicator to determine a position in the interpretation of the Qurâan. Fourth, every hypothetical (zhannÄ«) proposition in the QurâÄnic interpretation must not conflict with the certaint (qaá¹âÄ«) rational proposition in the theoretical Sufism. Fifth, Sufistic interpretation of the Qurâan is a particular form of a set of method of Qurâanic interpretation, which can be combined with the other methods, to achieve an eclectic and holistic interpretation of the Qurâan. The author also gives an example as the application of those five principles in the interpretation of the meaning of khalÄ«fah fÄ« al-ardh in al-Baqarah [2]: 30.